Cannabis-based extract for managing pain in dogs with osteoarthritis: efficacy and safety assessment - Griebeler, Neide Maria; Cremonese, Ricardo Penayo; Fakih Correa, Yasmin Rafaela; Pereira, Priscila Romero Mazzini; Rial, Amanda Furjan; Leite, Emanuela; Gonçalves, Maria Victoria Luz; Marques das Almas, Luiz Renato; Cardoso, Nedice Borges; Cezar-dos-Santos, Fernando; Toci, Aline Theodoro; Mojoli Le-Quesne, Andrés; et al. (Frontiers in Pharmacology, 2025)
IntroductionCanine osteoarthritis (OA) is a prevalent disease characterized by progressive joint degeneration, pain, and impaired mobility. In older dogs, OA affects approximately 80% of the population. Current pharmacological treatments are often limited in efficacy and may cause significant adverse effects. In this context, cannabinoids have emerged as a promising therapeutic alternative.MethodsThis double-blind, randomized study aimed to evaluate the efficacy and safety of a full-spectrum cannabis extract in managing OA-related pain and dysfunction in dogs. Seventeen dogs with OA were randomly assigned to receive either the cannabis extract (containing measured amounts of CBD, THC, CBG, CBC, and other cannabinoids) or a placebo for 90 days.ResultsAlthough the cannabis treatment did not significantly reduce pain levels according to the Helsinki Chronic Pain Index (HCPI) [F(1,14) = 0.001, p = 0.981, η2 = 0.000], a reduction of 2.4 points in HCPI scores compared to the placebo was observed at 90 days. Additionally, the treatment proved to be entirely safe, with no significant adverse effects reported. The few mild side effects observed resolved spontaneously within 24 h. Biomarker analysis revealed no significant differences between the cannabis and placebo groups.ConclusionOur findings suggest that full-spectrum cannabis extract containing CBD and THC is safe for use in dogs for up to 90 days. However, further research is needed to determine the optimal doses and formulations required to effectively alleviate OA-induced pain.